Study on Deformation Mechanism and Support Measures of Soft Surrounding Rock in Muzhailing Deep Tunnel - Zhigang Tao; Jindong Cao; Liu Yang; Aipeng Guo; Ruifeng Huang; Xiaojie Yang; Di Yuan; Lin Hou (Advances in Civil Engineering)
The deformation of Muzhailing deep tunnel is about 2.3 m in the process of construction, which is difficult to be controlled by the traditional “anchor-grouting integration” support system. This paper deeply analyzes the geological characteristics, rock mechanics characteristics, and surrounding rock failure characteristics of Muzhailing tunnel. The deformation mechanism and the failure of the support system are analyzed through the numerical simulation, theoretical analysis, and field test. The authors propose support measures suitable for Muzhailing tunnel based on the analysis results. The maximum buried depth is 600 m, and the engineering rock mass at the depth has nonlinear physical and mechanical phenomenon. The maximum principal stress of Muzhailing tunnel is 25.7 MPa, which belongs to high-stress joint swelling soft rock tunnel. The NPR cable can achieve large deformation under the condition of constant support resistance. The authors put forward the coupling support mode of “NPR cable + steel arch frame + concrete,” which is based on the idea of transforming the composite deformation mechanism to a single type. The stress concentration appears in the range of 12 m in the surrounding rock circle, and the lateral and vertical stress distributions are relatively symmetrical after the improved support. The circumferential strain of the surrounding rock is greatly reduced, and the range of strain is reduced by 10%. The field monitoring results show that the new support system can well control the large soft rock deformation of Muzhailing tunnel (0.5 m). The support strategy proposed can effectively control the large deformation and promote the formation of new support concept for deep tunnel.